Faith, Family, and Vulnerability: Religious and Ethnic Dimensions of Childhood Sexual Abuse in Nigeria - Wusu, Onipede; Olupooye, Olabusoye; Sulaman, Afolasade; Raji, Shakiru Olarotimi; Olateju, Kadijat E.; Aliu, Ibrahim Rotimi; Alausa, Moa-Liberty Waheed; Omobitan, Olufunsho (UIN Sunan Gunung Djati Bandung, 2024)
This study investigates the influence of ethnicity and family structure on childhood sexual abuse (CSA) experiences among women in Nigeria, with a particular focus on the moderating role of religious affiliation. Recognising the alarming national prevalence of CSA—estimated at 35%—the study addresses critical gaps in understanding how socio-cultural and familial variables intersect with religion to shape vulnerability. Using a cross-sectional, quantitative design, data were collected from 2,757 women across rural and urban areas in Nigeria’s six geopolitical zones through a multistage probability sampling method and structured electronic interviews. Descriptive, bivariate (Chi-square, Cramer’s V), and multivariate (logistic regression) analyses were conducted to assess the relationship between CSA, ethnicity, and family dynamics. Findings reveal that women from Igbo, Yoruba, and minority ethnic groups—particularly within Muslim and Christian communities—are significantly more likely to report CSA, especially those raised in polygynous households or by single parents or grandparents. Notably, Christians reported a higher prevalence of CSA than Muslims, suggesting religious variations in disclosure or exposure. These findings underscore the need for culturally and religiously sensitive interventions, policies, and child protection strategies that address ethnic and familial vulnerabilities. The originality of this study lies in its intersectional and nationally representative approach, offering a nuanced understanding that transcends the limitations of prior localised studies and contributes meaningful insights for policy and practice in child protection.